PERANCANGAN STRATEGI ORGANISASI BERBASIS BALANCED SCORECARD BAGI EDUKASI UNTUK BANGSA (EUB) KUALA LUMPUR, MALAYSIA - Lisa Darawati; Lindawati Kartika (STIE DWI SAKTI BATURAJA, 2017)
The Organization of Edukasi Untuk Bangsa (EUB), Kuala Lumpur, Malaysia has the goal of becoming an organization that provides training and certification for Indonesian Migrant Workers in various countries other than Kuala Lumpur. The purposes of this research are (1) To create harmonization / organizational alignment system for the organization of Edukasi Untuk Bangsa (EUB). (2) To arrange the KPI for the organization of Edukasi Untuk Bangsa (EUB). (3) To formulate a strategic map design from the Organization Edukasi Untuk Bangsa (EUB) based on the BSC approach. The sampling method is a nonprobability sampling with purposive sampling technique. The method of processing and data analysis are based on BSC using software expert choice. The results of this research indicated that the performance of Organization Edukasi Untuk Bangsa Kuala Lumpur Malaysia has obtained a value of 39.21 percent which can be expressed with red color. This performance can be improved by implementing a program of strategic initiatives, especially at the Key Performance Indicators that were still low.